ANALISIS TINGKAT KENYAMANAN SISWA KELAS V DALAM KEGIATAN MEMBACA DIAM (SILENT READING) DI SDN 3 MEKARJAYA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of student comfort in silent reading to support concentration and interest. However, many students at SDN 3 Mekarjaya initially showed restlessness and lack of focus during these activities. This study aims to determine the comfort level of fifth-grade students in silent reading at SDN 3 Mekarjaya. The methodology employed is quantitative research using a survey method. The research population consisted of 21 fifth-grade students, with the sample determined through total sampling. Data were collected via a closed Likert-scale questionnaire comprising 27 valid items with a very high reliability coefficient of 0.983. Data analysis involved descriptive statistics, including mean, median, mode, frequency distribution, variance, and standard deviation. The results indicate that the comfort level of fifth-grade students in silent reading is generally in the